Alcohol consumption and the risk of acute myocardial infarction in women. Issue 4 (August 1993) - Bianchi, C; Negri, E; La Vecchia, C; Franceschi, S
Abstract : STUDY OBJECTIVE–To investigate the relationship between alcohol consumption and the risk of acute myocardial infarction in women. DESIGN–This was a hospital based, case-control study carried out between 1983 and 1990. Main outcome measures were average daily number of drinks of various alcoholic beverages consumed and corresponding multivariate relative risk estimates and 95% confidence intervals (CI). SETTING–A network including major teaching and general hospitals in northern Italy. SUBJECTS–Cases were 298 women with acute myocardial infarction but no history of ischaemic heart disease and controls 685 women admitted to hospital for acute conditions, unrelated to alcohol consumption or to known or suspected risk factors for ischaemic heart disease. MEASUREMENTS AND MAIN RESULTS–Compared with non-drinkers, the estimated relative risks (RR) were 0.7 (95% CI 0.5, 1.0) for one drink or less per day, 0.8 (95% CI 0.6, 1.2) for more than one to two drinks per day, 1.4 (95% CI 0.8, 2.3) for more than two to three, and 2.6 (95% CI 1.5, 4.6) for more than three drinks per day. These estimates were consistent across strata of selected covariates, including age, education, and smoking. Allowance for major identified risk factors for myocardial infarction did not materially modify the risk estimate for light drinkers (RR 0.7, 95% CI 0.5, 1.1), but reduced the RR in heavy drinkers to 1.8 (95% CI 0.9, 3.5). CONCLUSIONS–This study indicates that women who do not drink alcohol have a risk of myocardial infarction that is higher than that of light drinkers, although the protection of light drinking was not significant. Among drinkers, however, there was a significant direct trend in risk with dose. The raised risks in heavy drinkers may reflect a real association or result from other unfavourable characteristics or habits associated with high alcohol consumption.